Climate Change Yields Groundwater Warming in Bavaria, Germany - Hemmerle, Hannes; Bayer, Peter (Frontiers in Earth Science, 2020)
Thermodynamic coupling between atmosphere and ground yields increasing aquifer temperatures as a consequence of global warming. While this is expected to manifest as a gradual warming in groundwater temperature time series, such continuous long-term recordings are scarce. As an alternative, the present work examines the use of repeated temperature-depth profiles of 35 wells in southern Germany, that were logged during campaigns in the early 1990s and in 2019. It is revealed that the temperatures have increased in nearly all cases. We find a moderate to good depth-dependent correlation to trends in air temperature, which however is strongly influenced by local hydrogeological and climate conditions. While during the last three decades, air temperatures have increased by a rate of 0.35 K (10a)-1 on average, the temperature increase in the subsurface is decreasing with depth, with median values of 0.28 K (10a)-1 in 20 m and only of 0.09 K (10a)-1 in 60 m depth. Still, the slow and damped warming of the groundwater bodies are remarkable, especially considering naturally very minor temperature changes in pristine groundwater bodies and predictions of atmospheric temperatures. This entails implications for temperature-dependent ecological and hydro-chemical processes, and also for the heat stored in the shallow ground. Moreover, it is demonstrated that the annual heat gain in the groundwater bodies below 15 m due to climate change is in the range of 10% of the state’s total heat demand, which underlines the geothermal potential associated with the change in natural heat fluxes at the ground surface.